Peran Pemimpin dalam Kebijakan Pembelajaran Selama Krisis COVID-19 - M. Risky Fauzi; Reni Matofiani (Lembaga Sosial Rumah Indonesia, 2022)
COVID-19 has had an impact on many areas of life, including education. This study aims to determine the role of leaders in learning policies in the COVID-19 crisis at SMAIT Al-Fityan School Gowa, South Sulawesi. This study uses a qualitative method. While the data collection using the method. The results showed that the stages of crisis management at SMAIT Al-Fityan School Gowa during the COVID-19 pandemic went through the following stages: crisis management planning included providing health education literacy by placing posters on how to wash hands properly in school corners; provide sink facilities for school residents to wash their hands before eating; and organize sports together for all school staff of Al-Fityan School every Wednesday. Then the management phase during the crisis includes the process of preventing and handling COVID-19 and policies to support the learning process. At the management stage after the crisis with the renewal of learning media and evaluation of learning outcomes.